Financial Literacy and Parental Income on the Personal Financial Management of Students with Love of Money as a Moderating Variable - Rossya fina Rohmaturrohmania; Maretha ika Prajawati (MEC-J (Management and Economics Journal), 2023)
Every intelligence that a student must have is intelligence in financial matters, including in terms of managing and managing his finances. The purpose of this study was to find out whether financial literacy and parental income influence student personal financial management, whether love of money affects financial literacy and student personal financial management, and whether love of money influences parental income and student personal financial management. This study uses quantitative research methods. The population to be taken were students from class 2019 to class 2022. The samples that the researchers would take from this study were 39. It can be concluded that there is an influence of parental income on financial management. There is no significant effect between love of money on financial literacy and student financial management. And referring to the last hypothesis also that the data results show that there is no significant effect between the love of money on financial literacy and student financial management.